Features of Destruction of Materials and Structures - Prof. Ph.D. Kasimova S.T; Assoc. Prof. Talipova N.Z; Assoc. Prof. Omonova D.F. (Peerian Journals Publishing, 2023)
During operation, most structures in buildings operate under loads. Damage is the initial stage of the destruction of individual structural elements, it is necessary to timely and accurately assess the nature and danger of damage to building structures. The study and classification of defects and damages makes it possible to take timely measures to eliminate structural defects and restore the building
Keywords: destruction; operation; defects; measures to eliminate defects